The influence of chronotopes on pre-service teachers' professional becoming in a school–university partnership. Issue 5 (17th August 2020) - Gutierrez, Amanda; Kostogriz, Alex
ABSTRACT: This article explores the influence of chronotopes on pre-service teachers' professional becoming in a school–university partnership model. It draws upon dialogue from professional conversations which included multiple stakeholders in the partnership. The results illustrate the complex process of becoming for pre-service teachers as they navigate voices across time and space. They provide an illustration of chronotopes interacting productively, providing support for pre-service growth, and chronotopes in tension, leading to the silencing of pre-service teacher voice. It is hoped this article encourages educators to reflect on the impact chronotopes can have on pre-service teachers' professional growth, the kinds of conditions that support growth and increased agency, and the ways chronoptic interactions can impact the development of transformative hybrid models of Initial Teacher Education.